APTrust Board Member Criteria (Version 1.0) - Tallman, Nathan (University of Virginia, 2026)
Competencies and qualifications for APTrust Governing Board members.
Original submission date: 2026-02-13T19:37:16Z
Keywords: Digital Preservation; Policy; Governance